Teacher Actions in Improving Early Childhood Literacy to Stimulate Critical Reasoning through Picture Cards - Pahenra; Wa Ode Sari Amalia; Usman; Yaman La Ndibo; Ridha Ichwantiy sabir (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2023)
Learning literacy in early childhood is the key needed by children to improve children's critical reasoning skills, with the media used as picture letter cards. because it is in accordance with the standard of learning in children, namely playing while learning and having fun. Accordingly, this research is remembered for its Class Action Research type which means improving children's literacy skills through picture cards by stimulating children's critical reasoning abilities. The results showed that there was an increase in children's literacy skills in Nambokido Kindergarten, Unaaha District, Konawe Regency through picture card games. There is a very significant increase using picture letter cards, which is 61.90% in cycle 1 to 85.71% in cycle II. For this situation, the increase is 23.81%. In line with that, it is very good that it can be assumed that early childhood literacy skills can be improved through picture letter cards games